Probe: Robert Moore’s Thought on Optimal Human Psychological Development, and Walter J. Ong’s Thought - Farrell, Thomas J. (New Explorations)

(untitled) (New Explorations Association, 2024)
In my deeply personal and candid probe I explore highlights of the thought of the late Jungian psychotherapist and theorist Robert Moore (1942-2016; Ph.D. in religion and psychology, University of Chicago, 1975) of the Chicago Theological Seminary. In addition, I explore highlights of the historical thought of the late American Jesuit Renaissance specialist and cultural historian and pioneering media ecology theorist Walter J. Ong (1912-2003; Ph.D. in English, Harvard University, 1955) of Saint Louis University – where I took five courses from him over the years.My favorite scholar is the American Jesuit Renaissance specialist and cultural historian and pioneering media ecology theorist Walter J. Ong (1912-2003; Ph.D. in English, Harvard University, 1955) of Saint Louis University – where I took five courses from him over the years.